Biotranformation Of Environmental Toxicants By Different Enzymes - Lopes, João Ricardo Marques (2022)
Pollution is currently one of the greatest global problems. Oxidoreductase enzymes have shown the capacity to transform hazardous chemical compounds. Investigating the ability of enzymes to transform environmentally concerning pollutants is essential to understand the toxicological role of those enzymes and for the development of novel bioremediation technologies. The present work studied the capacity of laccase, horseradish peroxidase (HRP), hemoglobin, and cytochrome c (Cc) to transform the azo dye methyl orange (MO), polycyclic aromatic hydrocarbons (PAHs), such as anthracene and benzo[a]pyrene (BaP), and the organophosphate pesticide chlorpyrifos. The use of the redox mediator ABTS in low concentrations (10 μM) increased MO decolorization by laccase over 10 fold, while the hemeproteins efficiently decolorized MO directly and the presence of ABTS afforded no benefit in these cases. Hemoglobin-catalyzed MO decolorization was followed by rapid inactivation of the hemeprotein. The presence of ABTS (50 μM) enabled laccase-catalyzed transformation of PAHs, for example, the oxidation of anthracene reaching 69 ± 4% in 24 h, and also enhanced anthracene transformation catalyzed by HRP. Cc exhibited the capacity to degrade various PAHs (77 ± 10% of anthracene and 70 ± 4% of BaP) without requiring mediator and the presence of ABTS (50 μM) was clearly disadvantageuos (5 ± 5% oxidation of anthracene). Despite the capacities shown by the enzymatic systems studied, none was able to transform chlorpyrifos. Further studies of the laccase-ABTS system showed that it was inhibited by the presence of Fe3+ ions and by humic acid, issues that can be problematic in the implementation of bioremediation processes. The results in this work indicate that hemoglobin and Cc potentially have a role in the metabolism of environmental toxicants by being able to transform PAHs and MO at neutral pH. Moreover, the presence of cardiolipin-containing membranes enhanced the peroxidase activity of Cc, including towards PAHs and the azo dye. These results support the hypothesis that Cc participates in the transformation of toxicants at the inner mitochondria membrane, where cardiolipin and Cc are located.